Analisis Perbandingan DER, ROA dan EVA pada Perusahaan Pertambangan Sebelum dan Sesudah Penerapan Peraturan Pemerintah No 1 Tahun 2014 Tentang Larangan Ekspor Mineral Mentah - Ariani Ariani; Andewi Rokhmawati; Ahmad Fauzan Fathoni (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2019)
The implemented of Government Regulation No.1 of 2014 concerning the ban on raw mineral exports aims to encourage companies to process mining products before they are sold. so that it is expected to be able to create added value that has an impact on the greater profits that will be obtained by the company. However, after this regulation was implemented, there was a decrease in the company's performance, which led to a decline in sales and a decline in the prices of mining companies' shares and an increase in the average debt in the mining sector. This study aims to determine the average difference in DER, ROA and EVA before and after the application of this Government Regulation. The population in this study were all mining companies listed on the Indonesia Stock Exchange in 2010-2017. Samples were collected on a purposive sampling technique from the criteria determined there were 26 samples selected. The data analysis method used is a different test of Willxocon Signed Rank Test using SPSS version 21. The results of this study indicate that: First there is no difference in DER for mining companies before and after the implementation of government regulations. Secondly there is a difference in ROA for mining companies after the application of government regulations. And thirdly there is a difference in EVA in mining companies after the implementation of government regulations in 2014.